Fear of Missing Out (FOMO) as a Predictor of Students’ Digital Well-Being: Evidence from Yogyakarta State University - Muhammad Nur Wangid; Chici Pratiwi; Agus Basuki; Fathur Rahman; Lintang Waskita Puri (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study examines the predictive role of Fear of Missing Out (FoMO) on digital well-being among university students in the post-pandemic digital era. A cross-sectional survey was conducted with 562 undergraduate students from Yogyakarta State University, Indonesia, selected through accidental sampling. Data were collected using the validated FoMO Scale and Digital Well-Being Scale, and analyzed using ordinal logistic regression. Results revealed that most students exhibited moderate levels of both FoMO (74.2%) and digital well-being (67.6%). Ordinal logistic regression demonstrated that FoMO significantly and negatively predicted digital well-being (χ² = 56.754, p < 0.001), with higher FoMO scores associated with lower digital well-being. The pseudo-R² values indicated that FoMO accounted for 7.5% to 13% of the variance in digital well-being, with the Wald test confirming FoMO as a significant predictor (p = 0.016). These findings establish FoMO as a significant psychological risk factor that undermines students' digital well-being through compulsive connectivity, emotional distress, and reduced self-regulation. The study underscores the urgent need for higher education institutions to integrate digital literacy programs, self-regulation training, and mental health support services to mitigate FoMO's adverse effects. These results contribute to digital well-being literature and offer practical implications for developing evidence-based counseling interventions in university settings. Keywords: Fear of Missing Out (FoMO), digital well-being, university students, mental health, higher education